The template synthesis, spectral characterizatin and thermal behaviour of new binuclear schiff base complexes derived from N-aminopyrimidine with 2,3butandione - Sönmez, Mehmet; Şkerci, Memet (My University, 2006)
A new series of two types of acyclic binuclear Schiff base complexes, prepared by template condensation of N-aminopyrimidine and 2,3-butandione in the presence of CuII, NiII, CoII and Zn II in n-BuOH solution, have been characterized by IR, elemental analyses, electronic spectral data, conductivity and magnetic measurements. From conductivity measurements, it is shown that the complex of Ni" is electrolyte. All the complexes have sub-normal magnetic moments commensurate with their binuclear nature. The thermal behaviour of the complexes has been studied by t.g. technique.
Keywords: Acyclic Schiff base complexes; Template synthesis